2023
DOI: 10.1021/acsapm.3c01485
|View full text |Cite
|
Sign up to set email alerts
|

Self-Curing Phthalonitrile Resin with Disulfide Bond as the Curing Group

Jianghuai Hu,
Yu Pu,
Rongtao Zhou
et al.

Abstract: To further investigate the presence of a radical mechanism in the curing process of phthalonitrile resins, a conventional radical initiation unit (disulfide segment) was introduced into phthalonitrile resins for the first time. A disulfide-bond-containing phthalonitrile monomer (DPBPN) was successfully synthesized. Its self-curing reaction could be promoted by disulfide segments in the precursor. Rheological measurements and differential scanning calorimetry showed that DPBPN exhibited a low melting point (124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In addition, for the perovskite + DMITU film, it can be found that a new peak at 567 cm −1 belongs to the S–S stretch vibration, which proves the interaction between two sulfur atoms in the perovskite + DMITU film. 38,39…”
Section: Resultsmentioning
confidence: 99%
“…In addition, for the perovskite + DMITU film, it can be found that a new peak at 567 cm −1 belongs to the S–S stretch vibration, which proves the interaction between two sulfur atoms in the perovskite + DMITU film. 38,39…”
Section: Resultsmentioning
confidence: 99%